Penerapan Hukum Kewenangan Audit Hukum Jaksa Pengacara Negara (JPN) Terkait Kesalahan Administrasi yang Berpotensi Merugikan Keuangan Negara - Saka Andriyansa; Moh. Muhlisin; Dominikus Rato; Y.A.Triana Ohoiwutun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law enforcement in the context of recovering state finances does not solely focus on corruption offenses, but also on administrative errors that may potentially cause losses to the state. The State Attorney (Jaksa Pengacara Negara/JPN) holds strategic authority through legal audits to identify, assess, and provide recommendations regarding potential state financial losses arising from administrative actions inconsistent with applicable regulations. This research formulates two main issues: first, how the legal authority of JPN is applied in conducting legal audits on administrative errors potentially causing state financial losses; second, what legal mechanisms are employed by JPN in conducting legal audits on such administrative errors. The findings of this study indicate that the implementation of legal authority by JPN through legal audits aims to ensure that every aspect of authority, procedure, and substance in governmental decision-making, as well as in the procurement of goods and services, complies with legal provisions, starting from the needs identification stage up to the final handover of work results. This is essential for JPN to accurately determine administrative errors that may potentially cause state financial losses and to formulate them in a legal audit report. The mechanism for resolving legal audit findings is carried out through coordination between JPN and the Government Internal Supervisory Apparatus (APIP) to determine the amount of potential losses. Subsequently, JPN provides recommendations to the applicant to return the potential losses to the state or regional treasury.